Cytogenetic follow‐up of chromosomal mosaicism detected in first‐trimester prenatal diagnosis. (8th April 2014) - Battaglia, Paola; Baroncini, Anna; Mattarozzi, Angela; Baccolini, Ilaria; Capucci, Antonella; Spada, Francesca; Pompilii, Eva; Pittalis, Maria Carla
ABSTRACT Objective To contribute to the risk assessment of true fetal mosaicism after detection of a mosaic chromosomal anomaly in chorionic villus samples (CVS) in order to enable more effective counseling and pregnancy management. Methods We retrospectively reviewed 7112 consecutive CVS analyzed on both direct preparations and cultured cells. In 135 out of the 177 cases of mosaicism, we performed cytogenetic follow‐up and determined the frequency of confined placental mosaicism (CPM) and true fetal mosaicism according to type and distribution of the cytogenetic abnormality. Results True fetal mosaicism was detected in 38 out of 135 cases (28.15%), confirming the higher incidence of CPM (71.85%). Confirmation rate of CV mosaicism depends on the combination of placental cell lineages affected, chromosome involved and mosaic versus non‐mosaic chromosomal anomaly. The overall probability of fetal involvement significantly rises with involvement of mesenchymal cells: 5.88% abnormal cytotrophoblast, 20.96% abnormal mesenchyme and 58.97% anomalies in both tissues. Conclusion Most of the mosaic findings at CVS are unreliable indicators of the fetal karyotype. Our study contributes to large series with cytogenetic information from the different tissues along the cytotrophoblast‐extraembrional mesoderm‐fetus axis in order to infer clinical relevance of the findings and to enable more effective genetic counseling. © 2014 John Wiley & Sons, Ltd.